Numerical demonstration of a transactive energy trading model for microgrids. Issue 4 (1st March 2022) - Crasta, Cletus; Mishra, Sambeet; Agabus, Hannes; Palu, Ivo; Wen, Fushuan
Abstract: Bidirectional power flow is becoming increasingly commonplace in modern distribution systems with the integration Renewable Energy Sources (RESs) and Energy Storage Systems (ESSs). This has facilitated in bringing generation closer to end‐consumers, thus leading to the emergence and rapid growth of microgrids. Additionally, due to the technological revolution in Information and Communications Technology (ICT), innovative business models have developed where willing and able participants of the power system can participate in the electricity market. In line with this evolution of both the electric power system and its participants, Energy‐as‐a‐Service (EaaS) is emerging as an increasingly prominent business model to address electrical grid challenges economically. EaaS encourages electricity grid customers to play a more active role and participate in different electricity markets. This paper introduces and simulates a variant of a Transactive Energy (TE) trading algorithm for microgrids. The paper describes the model in brief how multiple microgrids assets can trade electricity to ensure more efficient and economical local resource utilization. The main motivations of this research paper is to validate and test the suitability of the TE trading algorithm for a variety of conditions. The coordinated TE trading model can optimize expansion and investment planning especially at the distribution level.